(untitled) - Rubin, Allen; Babbie, Earl R (Pacific Grove, 1997)
Includes bibliography and index.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social service -- Research -- Methodology; Dịch vụ xã hội -- Phương pháp nghiên cứu